Respon Masyarakat Kalidoni Palembang terhadap Penari Wanita Pegon dalam Kesenian Kuda Lumping - Oktiviona Suci; Sri Suriana; Sholeh Khudin (Tanjak: Sejarah dan Peradaban Islam, 2024)
This research discusses a phenomenon in the Kuda Lumping art where there are female dancers called female pegon dancers. This phenomenon can contain various responses from the surrounding community. This research is qualitative research with a phenomenological approach. The primary data used in this research was obtained directly from the field through an interview process with the head of the Rt and the administration section of the Kalidoni sub-district office. The theory used in this research is the phenomenological theory by Edmund Husserl. The results of this research show that Kalidoni District has the art of Kuda Lumping in which there is a phenomenon of female Pegon dancers. Pegon female dancers, Kuda Lumping art, have changed the rules and appearance of Kuda Lumping art, especially in Kalidoni District, and is one of the traditional arts which in its development has received various responses from the community, both positive and negative, and some factors influence people's interest and there are impacts. or the influence of female pegon dancers.